2015
DOI: 10.1007/s10798-015-9318-z
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the correlation between social network analysis measures and performance of students in social network-based engineering education

Abstract: Social network-based engineering education (SNEE) is designed and implemented as a model of Education 3.0 paradigm. SNEE represents a new learning methodology, which is based on the concept of social networks and represents an extended model of project-led education. The concept of social networks was applied in the real-life experiment, considering two different dimensions: (1) to organize the education process as a social network-based process; and (2) to analyze the students' interactions in the context of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
64
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 43 publications
3
64
0
1
Order By: Relevance
“…On the other hand, the fact that these kinds of courses are both free and flexible also influences the degree of commitment, which is generally lower compared to a traditional setting. As commonly occurs (Putnik et al, 2015), those who participate more achieve a higher mark, as shown in Figure 4. Only 35 learners performed the two compulsory peer-reviewed activities, seven did only one, and 82 students did some activity in the platform such as visualizing videos or participating in the forum.…”
Section: Research Context: Course Descriptionmentioning
confidence: 77%
See 3 more Smart Citations
“…On the other hand, the fact that these kinds of courses are both free and flexible also influences the degree of commitment, which is generally lower compared to a traditional setting. As commonly occurs (Putnik et al, 2015), those who participate more achieve a higher mark, as shown in Figure 4. Only 35 learners performed the two compulsory peer-reviewed activities, seven did only one, and 82 students did some activity in the platform such as visualizing videos or participating in the forum.…”
Section: Research Context: Course Descriptionmentioning
confidence: 77%
“…At the same time, social networks have created conditions for the development of new paradigms and methodologies in education (Putnik et al, 2015) such as community-based learning or social learning.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By participating in an online social network, people who share common interests and goals can interact and exchange information and knowledge (Scardamalia & Bereiter, 2014 (Sharples, Kloos, Dimitriadis, Garlatti, & Specht, 2015), and provide new opportunities for designing and implementing advanced learning environments (Hwang, Wang, & Lai, 2015). Students' social interactions in online communities have contributed to the development of new paradigms and methodologies in education (Putnik et al, 2016).…”
Section: Social Networking Enhanced Learningmentioning
confidence: 99%